Disaster preparedness and Response in Zimbabwe: The case of Cyclone Idai of March 2019 in Chipinge and Chimanimani - Samutereko, Edmond Z. (Technium Social Sciences Journal, 2021)
It is the responsibility of the government of Zimbabwe and probably all nations to provide adequate protection for its citizens. It is actually a governance issue that needs serious attention. Despite the fact that the government is responsible, human suffering has been on the rise in most African countries including Zimbabwe as a result of the frequency and intensity of natural disasters. Disasters that have devastated most African countries have been drought, diseases, floods and tropical cyclones. Human risk to natural disasters cannot be completely eliminated but the effects can be minimised when there are early warning signs, preventative measures and if the emergency preparedness and response are in place and are fully funded. The natural disasters are not only caused by nature but human factor may be in play especially climate change that causes changes in the weather patterns. This has resulted in increased frequency and magnitude. This paper focuses on the Emergency preparedness and response in case of the natural disasters occurring. It looks into the case of Cyclone Idai that recently left more than 300 dead in Chimanimani and Chipinge in Zimbabwe. The figures of the causalities is very alarming and caused the international community to react. The Government through the responsible ministries could have done something to reduce its impact. The Hygo Framework for Action is used to assess the preparedness in Zimbabwe situation. It recommends community participation, funding and devolution as measures that enhances EPR plans to work.